2016
DOI: 10.1097/mjt.0000000000000374
|View full text |Cite
|
Sign up to set email alerts
|

Drug-Induced Subacute Cutaneous Lupus Erythematosus in a Patient Receiving Therapy for Chronic Hepatitis C

Abstract: Hepatitis C infection and its treatment have been associated with extrahepatic manifestations, including different skin conditions. Over the past decades, a greater number of drugs have been implicated as triggers for drug-induced subacute cutaneous lupus erythematosus. We report a case of a 42-year-old Hispanic man who developed a forehead violaceous rash during treatment with pegylated interferon alpha-2a as part of his therapy against hepatitis C infection that subsequently resulted to be subacute cutaneous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…37,38 De novo subacute cutaneous lupus erythematosus postantiviral treatment was described in two case reports, but a recent case report showed complete remission of discoid lupus erythematosus after initiation of antiviral treatment. [39][40][41] The role of antiviral treatment in these cutaneous manifestations is also intriguing. Previous studies have shown sustained virological response after antiviral treatment possibly reducing the risk of several extrahepatic manifestations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…37,38 De novo subacute cutaneous lupus erythematosus postantiviral treatment was described in two case reports, but a recent case report showed complete remission of discoid lupus erythematosus after initiation of antiviral treatment. [39][40][41] The role of antiviral treatment in these cutaneous manifestations is also intriguing. Previous studies have shown sustained virological response after antiviral treatment possibly reducing the risk of several extrahepatic manifestations.…”
Section: Discussionmentioning
confidence: 99%
“…An exacerbation of skin diseases after IFN-based AVT was reported in lichen planus, psoriasis, vitiligo, alopecia areata, and lupus erythematosus. 35,39,40,[45][46][47] Besides, Mahale and colleagues 44 found that the risk of lichen planus was not significantly reduced after achievement of sustained virological response. In this study, IFN-based AVT was found to mitigate the overall risk of CISD, especially psoriasis.…”
Section: Discussionmentioning
confidence: 99%